2008
DOI: 10.2165/00007256-200838090-00001
|View full text |Cite
|
Sign up to set email alerts
|

Talent Identification and Development Programmes in Sport

Abstract: Many children strive to attain excellence in sport. However, although talent identification and development programmes have gained popularity in recent decades, there remains a lack of consensus in relation to how talent should be defined or identified and there is no uniformly accepted theoretical framework to guide current practice. The success rates of talent identification and development programmes have rarely been assessed and the validity of the models applied remains highly debated. This article provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
573
3
38

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(662 citation statements)
references
References 63 publications
22
573
3
38
Order By: Relevance
“…Since chronological age and development rarely progress at the same rate [52], adequate training during puberty is an important factor to the future health development of young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Since chronological age and development rarely progress at the same rate [52], adequate training during puberty is an important factor to the future health development of young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many elite organisations place large financial investments into the identification and selection of talented juniors, 2 with the goal of subsequently providing the most appropriate learning environment to accelerate their identified potential. 3 Manifesting from this investment, many governing sport organisations host annual draft combines to facilitate the talent selection process, in which the most talented juniors (predominately under 18 years of age) are invited to partake in a range of tests purported to quantify their physical abilities and technical skills. One such organisation, the Australian Football League (AFL), facilitates a National Draft Combine each November, in which approximately 100 under 18 (U18) players are invited to participate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, scientific evidence has shown that aerobic fitness parallel the competitive development of youth soccer players (41,43,44).…”
Section: Introductionmentioning
confidence: 99%